Evaluation of In-Hospital Management of Pneumonia Patients - Daniyal Nagi , Asad Ali,Hafiz Mudabbar Mahboob, Mamoona Ghias , Saif-ur-Rehman , Hira Kareem (Journal of Rawalpindi Medical College, 2018)
Background: To audit the practices involved in the management of pneumonia patients in our settings and to compare them with standard recommended guidelines by the British Thoracic Society (BTS). Methods: In this cross-sectional study inclusion criteria were all patients admitted with suspicion of lower respiratory infection/pneumonia, with no exclusion. Clinical presentation, diagnostic workup, treatment modalities and complications were analyzed. Results: Majority (97.3%) of the patients were admitted through an emergency. Length of stay was less than 1 week in 72%. CURB-65 was applied in 2.6%. Majority (96% ) patients had inadequate investigations. Most commonly prescribed the first-line antibiotic was Cephalosporins given to 56%.. Co-morbidities were registered in 96%, which contributed towards expiry rate of 60%. Conclusion: The management of pneumonia patients in our settings is not in line with the recommended standard guidelines. This results in increased complications, prolonged hospital stay, and an overall poor prognosis.